Bränsleövervakningssystem för marina fartyg - Johansson, Daniel; Olsson, Tobias (My University, 2014)
This report focus on the development of a system that allows the user to monitor the fuel consumption of a marine vessel. The aim with this project is a functional demo that is user friendly and reliable. The showing results should be accurate to the fuel consumption of that vessel. To install this demo in a marine vessel is not a part of the project but the development will take this in consideration. Through this report the approach and background of the project is described from beginning to the final result. The result was a demo that meets all requirements for this project but leaves some opinions on improvements that should be considered if further development would take place. The main areas are judged to be more cooperation between NMEA 2000 and the system, additional parameters with configurable and further development of the Android application.
Keywords: Data- och informationsvetenskap; Computer and Information Science